Maternal and infant anthropometric characteristics correlated to protein concentration of colostrum and mature milk: a longitudinal study - Solange Valdivia, L. (2017)
Objective: To determine maternal and infant anthropometric characteristics correlated to protein concentration of colostrum and mature milk in the Hospital "El Carmen", Huancayo Method: analytical, correlational longitudinal study; Shows: 35 (mothers and infants) who met the selection criteria. Instrument: data collection sheet consigning maternal anthropometric measurements, infant and results of protein concentration of colostrum and mature milk; measurement variables in two phases (Al childbirth and fourth month postpartum). Spearman correlation R, Pearson and multivariate logistic regression was used. Results: The median age of the mothers was 20 years, mean BMI was pre- gestational 23.55, median pre- delivery was 26.71, and fourth month postpartum was 24.42; In infants the predominant female sex was 54.29%, the median birth weight was 3,030 kg and at 4 months had an average weight of 6,580 kg. The bivariate analysis showed statistical significance between protein concentration of colostrum and fourth month weight (p = 0.0119) and the protein concentration of mature milk with respect to the size of the infant to four months (p = 0.0041). Multivariate for birth weight, analysis is related to the gestational Body Mass Index Pre (p <0.011), R2: 0.481. Conclusion: The anthropometric characteristics of the mother and infant are correlated to protein concentration of colostrum and mature milk Keywords: Body mass index, Newborn, Birth weight, Breast Milk, Proteins.